General Considerations of Ruptured Abdominal Aortic Aneurysm: Ruptured Abdominal Aortic Aneurysm - Lee, Chung Won (The Korean Society for Thoracic and Cardiovascular Surgery, 2015)
Although development of surgical technique and critical care, ruptured abdominal aortic aneurysm still carries a high mortality. In order to obtain good results, various efforts have been attempted. This paper reviews initial management of ruptured abdominal aortic aneurysm and discuss the key point open surgical repair and endovascular aneurysm repair.